2017
DOI: 10.1186/s10194-017-0778-2
|View full text |Cite
|
Sign up to set email alerts
|

Anodal transcranial direct current stimulation over the left temporal pole restores normal visual evoked potential habituation in interictal migraineurs

Abstract: BackgroundNeuroimaging data has implicated the temporal pole (TP) in migraine pathophysiology; the density and functional activity of the TP were reported to fluctuate in accordance with the migraine cycle. Yet, the exact link between TP morpho-functional abnormalities and migraine is unknown. Here, we examined whether non-invasive anodal transcranial direct current stimulation (tDCS) ameliorates abnormal interictal multimodal sensory processing in patients with migraine.MethodsWe examined the habituation of v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 45 publications
2
16
0
Order By: Relevance
“…Results from numerous prior studies are consistent with a central role of the temporal lobe in the psychophysiology and cyclical recurrence of migraine [19,[60][61][62][63][64].…”
Section: Pre-post Changes In Cortical Thicknesssupporting
confidence: 61%
“…Results from numerous prior studies are consistent with a central role of the temporal lobe in the psychophysiology and cyclical recurrence of migraine [19,[60][61][62][63][64].…”
Section: Pre-post Changes In Cortical Thicknesssupporting
confidence: 61%
“…If hyper-responsiveness in migraine were to be considered as resulting from of a network dysfunction rather than a primary local phenomenon, novel therapeutic opportunities may arise. Indeed, as shown in recent studies, dorsal fronto-parietal areas can causally modulate the activity of visual areas ( 35 ) and anodal transcranial direct current stimulation of the left temporal pole is able to normalize visual responses in migraine patients ( 50 ). Rather than targeting the primary visual cortex, which yielded equivocal results in therapeutic trials ( 48 ), non-invasive neurostimulation of other areas in the visual attention network could be more effective for the preventive treatment of migraine.…”
Section: Discussionmentioning
confidence: 85%
“…The TP was hyperexcitable with painful heat stimulation and showed increased resting-state connectivity with hypothalamic in interictal migraine patients, indicating that TP may be involved in the interictal hypersensitivity to pain, smell and light [ 40 , 41 ].In another fMRI study, increased average regional homogeneity values in TP showed significantly positive correlations with disease duration of MO [ 42 ]. During odour stimulation in a H(2)(15)O-PET study, migraineurs showed significantly higher activation than controls in the left TP, suggesting a role in olfactory hypersensitivity of migraine [ 43 ].A recent study found that enhancing excitability of the TP with non-invasive anodal transcranial direct current stimulation normalized abnormal interictal visual information processing in migraineurs [ 44 ], supporting TP as a possible therapeutic target to relieve hypersensitivity of migraine. Our study further provides evidence of TP perfusion abnormality in interictal migraine and this structure needs deeper investigation.…”
Section: Discussionmentioning
confidence: 99%